Biodegradation of bisphenol-A (BPA) in activated sludge batch reactors: Analysis of the acclimation process - Ferro Orozco, Ana Micaela (2013)
In this work the effect of (a) the sludge age (SA) and the acclimation strategy on the acclimation process of activated sludge (AS) to bisphenol A (BPA), (b) the presence of biogenic substrates on the degradation of BPA, and (c) the acclimation on the degradation of biogenic substrates was studied. AS samples from reactors operated at SA of 30 and 45d were acclimated to BPA using two strategies: constant or increasing the initial BPA concentration. Although acclimation to BPA was achieved using both strategies, no net biomass growth was detected. Specific BPA degradation rate of acclimated AS ranged between 65 and 90mgBPAgTSS-1d-1. BPA degradation was not affected by the biogenic substrates cheese whey or acetate; acclimation to BPA did not cause a negative effect on the biodegradation of these substrates. During the degradation of cheese whey, specific mean oxygen uptake rate (qo2mean) and specific mean substrate consumption rate (qSmean) of non-acclimated AS were similar to those corresponding to acclimated ones. When acetate was tested, qo2mean and qSmean values corresponding to acclimated AS were about twofold the values of the non-acclimated ones. This enhancement could occur because acetate is an intermediate of the metabolism of BPA.